Hubungan Dukungan Keluarga dengan Manajemen Diri Penyakit Hipertensi di Puskesmas Sikumana Kecamatan Maulafa Kota Kupang - Yoany Maria V.B. Aty; Maria Ingrida Lavenia Suni; Dominggos Gonsalves; Maria Sambriong; Teresia Elfi (Poltekkes Kemenkes Mataram, 2022)
Background: Hypertension is still a problem in the world and developing countries. Hypertension is the number one cause of death globally. This problem will continue to arise if the patient does not have regular control and hypertension checks must be carried out continuously with the aim of maintaining normal blood pressure levels and accompanied by lifestyle changes. Objective: To determine the relationship between family support and management of hypertension in Sikumana Health Center, Maulafa District, Kupang City. Methods: This type of research is a quantitative research with a cross sectional design. The population is hypertensive patients who conduct examinations at the Sikumana Health Center, Maulafa District, Kupang City, the sample used is 175 respondents, data collection using a questionnaire. Results: Family support has the most appropriate category as many as 4 respondents (2.3%), enough as many as 8 respondents (4.6%) and the less category as many as 163 respondents (93.1%), while self-management is the most appropriate category 12 respondents (6.9%), sufficient as many as 59 respondents (33.7%) and less as many as 104 respondents (59.4%). The results of the chi square test obtained a P value of 0.02 which stated that there was a significant relationship between family support and self-management of hypertension at the Sikumana Health Center, Maulafa District, Kupang City. Conclusion: The majority of respondents family support for hypertension sufferers at the Sikumana Health Center, Maulafa District, Kupang City is in the sufficient category, the majority of the respondents for self-management of hypertension sufferers at the Sikumana Health Center Maulafa District, Kupang City is in the less category. The results of the analysis show that there is a significant relationship between family support and management. self-hypertension at the Sikumana Health Center, Maulafa District, Kupang City.